Contrast-enhanced MRI of the wrist: Intravenous application of gadolinium improves diagnosis in ulnar-sided injuries of the TFCC. Issue 143 (October 2021) - Luetkens, Karsten Sebastian; Laas, Susanne Franziska; Haßler, Sylvia; Gassenmaier, Tobias; Gietzen, Carsten Herbert; Christopoulos, Georgios; Huflage, Henner; Kunz, Andreas Steven; Bley, Thorsten Alexander; Schmitt, Rainer; Grunz, Jan-Peter
Highlights: Superior assessability is feasible with contrast-enhanced, fat-saturated T1 TSE. Contrast-to-noise ratio improves after intravenous gadolinium application. Access to contrast-enhanced T1 TSE increases accuracy for peripheral TFCC lesions. Abstract: Purpose: Although lesions of the triangular fibrocartilage complex (TFCC) frequently induce ulnar-sided wrist pain and potentially distal radioulnar joint instability, diagnosis can pose a challenge due to the intricate anatomy. This study aims to evaluate the benefits of contrast-enhanced sequences for the detection of TFCC injuries in magnetic resonance imaging of the wrist. Method: 94 patients underwent wrist MRI with intravenous application of gadolinium-based contrast agents. For each patient, two datasets were analysed independently by two board-certified radiologists: One set comprised only plain T1- and fat-saturated proton-density-weighted sequences, while the second dataset included contrast-enhanced T1-weighted images with fat suppression. Arthroscopy or clinical reports served as reference standard with the former being used whenever available. Diagnostic confidence and TFCC component assessability were subjectively evaluated. Contrast-to-noise ratios (CNR) were calculated serve as an objective indicator of image contrast. Results: Lesions of the articular disc, the foveal and styloid ulnar attachment were present in 24 (25.5%), 61 (64.9%) and 53 (56.4%) patients. Access to contrast-enhanced T1 images improved the diagnostic accuracy for injuries of the styloid (R1/R2, 0.68/0.73 vs. 0.86/0.88) and foveal attachment (0.68/0.72 vs. 0.90/0.89) substantially compared to plain MRI (all p < 0.001), while no benefits could be identified for lesions of the central disc (0.89/0.90 vs. 0.87/0.90). Readers' diagnostic confidence and CNR for ulnar-sided lesions improved with contrast-enhanced T1 sequences available (p < 0.001). Conclusions: With superior CNR in lesions of the TFCC's foveal and styloid attachment, contrast-enhanced, fat-saturated T1-weighted sequences facilitate higher diagnostic accuracy and confidence than fat-saturated PD- and plain T1-weighted MRI.